ARCGIS STORYMAPS IN GEOGRAPHY LEARNING: A SYSTEMATIC LITERATURE REVIEW - Tusam, Mohamad; Somantri, Lili; Setiawan, Iwan; Sugito, Nanin Trianawati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This systematic literature review examines the use of ArcGIS StoryMaps in the context of high school geography education, with a particular focus on the methods of implementation, the resulting impact, and the benefits derived from their use. ArcGIS StoryMaps provides an innovative platform for the creation of interactive and engaging geographic content, given the increasing influence of digital tools in the educational landscape. The findings of the eleven studies selected from the 290 articles are presented in this review. The studies highlight the ways in which ArcGIS StoryMaps enhances student engagement, spatial thinking, and comprehension of geographic concepts. The tool is compatible with a variety of learning approaches, including project-based, inquiry-based, and case-based learning. Furthermore, it facilitates digital learning environments through immersive and dynamic presentations. The findings indicate that ArcGIS StoryMaps not only facilitates students' comprehension and creative capabilities but also assists educators in enhancing their pedagogical approaches and geographic expertise. However, the limitations of the study, such as the focus on positive effects, may affect the generalizability of the findings. It would be beneficial for future research to address these limitations by examining potential implementation challenges. In conclusion, ArcGIS StoryMaps has the potential to revolutionize geography education by enhancing the learning process in both engagement and efficiency.